2016
DOI: 10.1021/acs.jctc.6b00480
|View full text |Cite
|
Sign up to set email alerts
|

Equation of Motion Theory for Excited States in Variational Monte Carlo and the Jastrow Antisymmetric Geminal Power in Hilbert Space

Abstract: An equation of motion formalism for excited states in variational Monte Carlo is derived and a pilot implementation for the Jastrow-modified antisymmetric geminal power is tested. In single excitations across a range of small molecules, this combination is shown to be intermediate in accuracy between configuration interaction singles and equation of motion coupled cluster with singles and doubles. For double excitations, energy errors are found to be similar to those for coupled cluster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…(5) VMC, and in general are much more expensive to evaluate than the first derivatives that are used in both ground state VMC [13][14][15] and EOM-VMC. 7 To avoid the explicit evaluation of wave function second derivatives, we will therefore adopt a finite difference approximation to our EOM ansatz,…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…(5) VMC, and in general are much more expensive to evaluate than the first derivatives that are used in both ground state VMC [13][14][15] and EOM-VMC. 7 To avoid the explicit evaluation of wave function second derivatives, we will therefore adopt a finite difference approximation to our EOM ansatz,…”
mentioning
confidence: 99%
“…7 In our previous work minimizing Ω for the JAGP, we found that it can be quite challenging to choose a good initial guess for the excited state. In our work on EOM-JAGP, we observed unacceptably large biases in favor of the ground state, the origin of which can be traced to its accuracy for ground states despite its compact parameterization.…”
mentioning
confidence: 99%
See 3 more Smart Citations